A suicide attentional bias as implicit cognitive marker of suicide vulnerability in a high-risk sample - Brüdern, Juliane; Spangenberg, Lena; Stein, Maria; Gold, Helena; Forkmann, Thomas; Stengler, Katarina; Glaesmer, Heide (Frontiers in Psychiatry, 2024)
Introduction: Suicide risk assessment based on self-report questionnaires is considered as problematic because risk states are dynamic and at-risk individuals may conceal suicidal intentions for several reasons. Therefore, recent research efforts increasingly focus on implicit risk markers such as the suicide attentional bias (SAB) measured with the Suicide Stroop Task (SST). However, most SST studies failed to demonstrate a SAB in individuals with suicide risk and repeatedly demonstrated insufficient psychometrics of the SST. This study aimed to investigate a SAB using a modified SST (M-SST) and to test its psychometric properties. Method: We compared n = 61 healthy controls and a high-risk inpatient sample of n = 40 suicide ideators and n = 40 suicide attempters regarding interference scores of positive, negative and suicide-related words. Interference scores were calculated by subtracting the mean reaction time (mean RT) of the neutral words from the mean RT of the suicide-related words (mean RT Suicide –mean RT Neutral), resulting in a suicide-specific interference score. Similarly, interference scores were calculated for the positive and negative words by subtracting the mean RT of neutral words from the mean RT of positive and negative words. Results: A Group × Interference ANOVA showed a significant interaction effect (p <.001, ηp2 = .09), indicating that group effects significantly vary across interference type. Post hoc comparisons revealed that both ideators and attempters demonstrated greater interferences only for suicide-related words compared to healthy controls, indicating a SAB in patients, while a difference between ideators and attempters was lacking. The suicide interference score classified with an AUC = 0.73, 95% CI [0.65 – 0.82], p <.001, between controls and patients with STBs. The M-SST demonstrated good internal consistency and convergent validity. Discussion: The study adds evidence to the assumptions of the Cognitive Model of Suicide, viewing a SAB as a cognitive marker of suicide vulnerability independently of the engagement in suicidal behavior. The results’ clinical implications are discussed in the context of recommended intervention strategies during an acute suicidal state. Future studies with the M-SST should include non-suicidal patient controls to investigate whether a SAB is uniquely related to suicidality.